The study of quality of life in patients with coronary artery disease using the SF-36 questionnaire - G. S. Mal; M. V. Dudka; O. Yu. Bushueva; M. A. Bykanova; I. M. Letov (Izdatelstvo OKI, 2018)
It was conducted a simple prospective study of the effect of lipid-lowering therapy in the assessment of quality of life using the SF-36 in IHD in men before and after pharmacological intervention. We did not have a statistically significant difference in the dynamics of scales SF-36 questionnaire both before treatment and after in patients with coronary heart disease, stable angina FC I-II with atherogenic GLP-sensitive rosuvastatin treatment, in comparison with a group of patients who switched to bi-component therapy. However, in the analysis of the personal data of patients with coronary artery disease based on genotype found that the original values of quality of life on the scale of SF-36 in media D allele polymorphism ACE I/D is different from that in comparison with the native I allele. Thus, patients are carriers of D allele showed initially a bad score for quality of life and less dynamic values on the scales of SF-36, regardless of the type of pharmacological correction of disorders of lipid metabolism. Therefore, from the point of view of preventive approach is of interest to link genetic and personal-behavioral characteristics considered as psychological factors of CHD risk.